2019
DOI: 10.1007/s10800-019-01332-z
|View full text |Cite
|
Sign up to set email alerts
|

Electroreduction of carbon dioxide to formate at high current densities using tin and tin oxide gas diffusion electrodes

Abstract: We investigate tin (Sn) and tin oxide (SnO 2 ) nanoparticle catalysts deposited on gas diffusion layers for the electrochemical reduction of carbon dioxide (CO 2 ) to formate. The performance and durability of these electrodes was evaluated in a gas-fed electrolysis cell with a flowing liquid electrolyte stream and an integrated reference electrode. The SnO 2 electrodes achieved peak current densities of 385 ± 19 mA cm -2 while the Sn electrodes achieved peak current densities of 214 ± 6 mA cm -2 , both at a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 76 publications
(119 reference statements)
0
52
0
1
Order By: Relevance
“…For all experiments, Ag‐GDE cathodes were loaded into the cell shown in Figure (bottom) along with a metallic Ni anode and a Hg/HgO reference electrode to enable independent measurement of individual electrode polarizations. The cell geometry was originally developed by our group as a small‐scale redox flow battery testing platform and was recently adapted for a catalytic study of tin and tin oxide GDEs for electroreduction of CO 2 to formate in a gas‐fed, flowing alkaline electrolyte configuration . In this study, the cathode side was outfitted with a serpentine flow field machined from polymer‐impregnated graphite and operated in gas‐phase delivery mode.…”
Section: Resultsmentioning
confidence: 99%
“…For all experiments, Ag‐GDE cathodes were loaded into the cell shown in Figure (bottom) along with a metallic Ni anode and a Hg/HgO reference electrode to enable independent measurement of individual electrode polarizations. The cell geometry was originally developed by our group as a small‐scale redox flow battery testing platform and was recently adapted for a catalytic study of tin and tin oxide GDEs for electroreduction of CO 2 to formate in a gas‐fed, flowing alkaline electrolyte configuration . In this study, the cathode side was outfitted with a serpentine flow field machined from polymer‐impregnated graphite and operated in gas‐phase delivery mode.…”
Section: Resultsmentioning
confidence: 99%
“…The cell geometry was originally developed by our group as a small-scale redox flow battery testing platform [44] and was recently adapted for a catalytic study of tin and tin oxide GDEs for electroreduction of CO2 to formate in a gas-fed, flowing alkaline electrolyte configuration. [45] In this study, the cathode side was outfitted with a serpentine flow field machined from polymer-impregnated graphite and operated in gas-phase delivery mode. The serpentine flow field both provides electrical contact to the GDE and facilitates liquid removal by flowing gas, which allows experiments to continue until the advanced stages of electrode flooding.…”
Section: Co2 Electrolysis and Capacitance Measurementsmentioning
confidence: 99%
“…Hydrogen evolution was observed during all electrolyses and is assumed to be the main unfavourable side reaction limiting the current efficiency. [13,15,16,27] However, formation of CO as it has been reported as alternative side reaction besides hydrogen evolution [13] cannot be excluded, but has not been examined.…”
Section: Co 2 Electrolysis To Formatementioning
confidence: 99%
“…Thereby, Sn was applied as main electro-catalyst in the GDE. [13][14][15][16][17][18] In batch processes, FE up to 90 % have been reported at current densities in range of À 50 to À 200 mA cm À 2 . [13] In continuous processes, several studies demonstrated FE between 70 und 75 % at current densities as high as À 100 to À 400 mA cm À 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation